Pengaruh Desain Kerja dan Kepribadian Terhadap Keadilan Kerja Guru di SMP Negeri Provinsi Daerah Khusus Ibukota (DKI) Jakarta - Tonny Sinaga; Matin Matin; Francis Tantri (Jurnal Ilmiah Wahana Pendidikan, 2021)
The purpose of this study is to gain sufficient in formation on the effect of Job Design and Personality on the Teacher’s Work Justice in State Junior High School Provincial Government of DKI Jakarta.This study consisted of too exogenous variable, they are Job Design and Personality and endogenous variable is justice of the teacher jobs in State Junior High School Provincial of DKI Jakarta.This research conducted in Jakarta for six months, since January to June 2018.The population of this research was all of the teachers in state Junior high school Provincial Government of DKI Jakarta, they were respondents. The sample was taken by applying simple random sampling. The total sample of this research was 222 teachers. The result of research showed that ( 1 ) There is a significant direct effect of job design to work justice ( 2 ) There is a significant direct effect of personality to work justice ( 3 ) There is a significant direct effect of job design to personality. Based on the result of this research,the researcher suggested to the teacher in order to improve the organizational structure and personality in school organization so they could justice and finally they finding high motivation works and job high performance.